Perlindungan Hukum Terhadap Pekerja Konstruksi melalui Pemenuhan Jaminan Sosial - Septian Juliansyah; Vina Mardhotillah; Silfanny Alvionita; Delis Apriyani (Journal of Industrial Relations Studies, 2026)
Indonesian workers currently really need social security for their work safety. With social security, it will have a good impact on the survival of their families in the future. If one day a work accident occurs to the worker while they are carrying out their duties, family members can enjoy financial assistance from the government through the BPJS Ketenagakerjaan guarantee program. Basically, this social security will also benefit construction companies in improving the welfare of their employees. The research uses a normative juridical method with a statute approach and a conceptual approach, secondary data is obtained through literature studies in the form of laws, legal journals, and court decisions related to social protection for construction workers. BPJS Ketenagakerjaan has the task and function to organize Employment Social Security through 5 Programs, namely Work Accident Insurance (JKK), Job Loss Insurance (JKP), Old Age Security (JHT), Pension Insurance (JP), and Death Insurance (JKM)